ASSESSMENT ON CUSTOMER SATISFACTION ON DISCOVERY SUITES IN PASIG CITY: BASIS FOR SERVICE QUALITY IMPROVEMENT (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Social media has emerged as a crucial platform for businesses, especially in the hospitality sector, to advertise their services, engage with customers, and cultivate brand loyalty. Although it presents challenges, such as the risk of negative feedback and customer dissatisfaction, social media marketing continues to be a widely adopted strategy. It offers various benefits, helping businesses to stand out and stay competitive in a crowded market. This chapter provides a comprehensive discussion of the research design adopted by the researchers, detailing the profile of the respondents, the research instruments utilized, the data collection methods, and the statistical techniques applied to analyze the data. Based on the summary of findings and conclusions, the following recommendations are proposed:  Optimize elevator management to reduce congestion, shorten queue times, and enhance the overall guest experience, especially during peak transportation periods. Expand the parking facilities to better accommodate guests' vehicles, ensuring greater convenience and minimizing traffic congestion. Upgrade Wi-Fi services to ensure fast and reliable connectivity, addressing guest dissatisfaction and significantly improving their stay. Maintain consistent room and water temperatures by resolving issues related to fluctuating hot and cold water supply, ensuring guest comfort and satisfaction. Provide complimentary grooming kits to meet guest needs and enhance their overall experience, reinforcing attention to detail and customer care. From the findings and data collected, the following conclusions were made:  Elevator delays occur due to occasional breakdowns, resulting in long wait times that inconvenience guests who are eager to reach their rooms. Insufficient parking spaces create challenges and frustration for guests, particularly during peak periods or events, leading to difficulty in finding parking. Wi-Fi connectivity issues are noted, as guests expect continuous and reliable internet access during their stay, with disruptions causing dissatisfaction. Fluctuating room temperatures cause discomfort, impacting sleep quality and diminishing overall guest satisfaction with their stay. The lack of essential amenities, such as combs and shaving kits, leaves guests feeling that their needs are not fully met, potentially affecting their overall experience.
Keywords: elevator delays; breakdowns; long wait times; insufficient parking; frustration; peak periods; wi-fi connectivity issues; reliable internet access; fluctuating room temperatures; sleep quality; lack of essential amenities; combs; shaving kits; guest